Diagnosis of Congenital Hypothyroidism by Analysis of Medical Records - Linda Handayuni; Dewi Mardiawati; Ririn Afrima Yenni; Rozi Rahmadian (Jurnal Penelitian Pendidikan IPA, 2023)
Congenital hypothyroidism is one of the causes of mental retardation in children that can be prevented if recognized and treated early. Thyroid hormones play a role in the development of the central nervous system. It is known that 95% of CH do not show typical clinical signs and symptoms at birth and the duration of early intervention to prevent mental retardation is short. Therefore, most developed countries have conducted neonatal screening programs for early detection of CH. The purpose of this study was to determine the diagnosis and management of congenital hypoteroid based on medical record analysis. This research method is a cross-sectional descriptive study with a quantitative approach to patient medical records. Data were analyzed in accordance with the standard diagnosis and management of congenital hypoteroid issued by the Pediatric Association in 2017. The clinical practice guidelines explain that congenital hypothyroidism can be transient or permanent and is classified according to the location of the disorder: primary (in the thyroid gland) or secondary (in the pituitary and/or hypothalamus); severity of hypothyroidism: (serum TSH levels > 100 mIU/L are considered severe; and age of onset of hypothyroidism. The most common form is permanent primary CH (high serum TSH levels) due to thyroid dysgenesis. Permanent CH requires lifelong treatment while transient CH does not. The results of the study have met clinical guidelines, namely CH screening in newborns is positive if the TSH level is â‰¥ 20 mU/L. Infants with positive screening results must be confirmed by re-checking serum TSH and FT4. The diagnosis of CH is made when TSH levels are high and FT4 is low. In non-screened infants, the diagnosis is made through clinical symptoms and serum TSH and FT4 examination.